Respuesta :

  9x - y = 5
7x - 6y = 5

Solve both equations for one variable. I'll solve for y.

9x - y = 5            Subtract 9x from both sides
      -y = -9x + 5   Divide both sides by -1
       y = 9x - 5

7x - 6y = 5   Subtract 7x from both sides
      -6y = -7x + 5   Divide both sides by -6
          y = [tex] \frac{7}{6} [/tex]x - [tex] \frac{5}{6} [/tex]

Since both equations equal y, you can set them equal to each other and solve for x.

9x - 5 = [tex] \frac{7}{6} [/tex]x - [tex] \frac{5}{6} [/tex]   Multiply both sides by 6 to eliminate the fractions
54x - 30 = 7x - 5    Subtract 7x from both sides
47x - 30 = -5          Add 30 to both sides
       47x = 25          Divide both sides by 47
           x = 
[tex] \frac{25}{47} [/tex]

Now, plug that x-value into the x of either equation. I'll plug it into 9x - y = 5.

9x - y = 5   Plug in the x-value
9([tex] \frac{25}{47} [/tex]) - y = 5   Multiply
[tex] \frac{225}{47} [/tex] - y = 5   Subtract [tex] \frac{225}{47} [/tex] from both sides
-y = 0.21276595744 (I had to convert it to a decimal)   Divide both sides by -1
 y = -
0.21276595744

So, the answer to the system is (
0.53191489361, -0.21276595744)